SUMMARY OF CONSUMER PRODUCT EXAMINATIONS CONDUCTED BY RFCFS OF THE MINISTRY OF JUSTICE OF THE RUSSIAN FEDERATION IN 2012–2013 - A. Selivanov (Теория и практика судебной экспертизы, 2015)
The paper sums up RFCFS's record in conducting forensic commodity examinations involving different product categories.